1976
DOI: 10.1192/bjp.129.5.497
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Treatment of Orgasmic Dysfunction: A Controlled Study

Abstract: Twenty-two anorgasmic women received 20 sessions of a multiple-technique behavioural therapy. The design included blind ratings by two independent assessors, multiple assessment instruments, and a waiting list control group. Treatment was significantly better than no treatment in terms of: (1) the percentage of patients experiencing orgasm during at least 50 per cent of sexual relations; (2) the percentage of women reporting satisfactory sexual relations at least 50 per cent of the time; (3) patients' ratings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Since then, limited progress has been made in investigating the efficacy and ingredients of various forms of treatment for sexual dysfunction, together with the influence of certain client characteristics upon their outcome (Jehu, 1979). Notable among the few contributions to date are the investigations conducted by Munjack, et al (1976) and Mathews, et al (1976). In the former study with women complaining of orgastic dysfunction, there was greater improvement among those given individually tailored behavioural treatment compared to other subjects who remained on a waiting list for treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, limited progress has been made in investigating the efficacy and ingredients of various forms of treatment for sexual dysfunction, together with the influence of certain client characteristics upon their outcome (Jehu, 1979). Notable among the few contributions to date are the investigations conducted by Munjack, et al (1976) and Mathews, et al (1976). In the former study with women complaining of orgastic dysfunction, there was greater improvement among those given individually tailored behavioural treatment compared to other subjects who remained on a waiting list for treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Masters and Johnson (1970) achieved high success rates with the largest series of sexually dysfunctional patients ever reported; however, because of the uncontrolled nature of their study, we do not know how well these patients would have fared if they had received other forms of treatment or no treatment at all. Notable among the few contributions to date are the investigations conducted by Munjack, et al (1976) and Mathews, et al (1976). Since then, limited progress has been made in investigating the efficacy and ingredients of various forms of treatment for sexual dysfunction, together with the influence of certain client characteristics upon their outcome (Jehu, 1979).…”
Section: Major Tranquilizersmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies provide no information on the comparability of treatment groups prior to treatment (e.g. Munjack et al 1976;Crowe et al 1981).…”
Section: Methods Of Controlling Prognostic Variability -The Avoidancementioning
confidence: 99%
“…This approach has shown potential for individuals suffering from anxiety related to sexual activities including Acquired FOD caused by anxiety. While some studies have shown that systematic desensitization is better than assertion training or a waiting list, others have found that this approach helps improve sexual anxiety but not orgasm functioning and yet others have reported effects similar to DM [58–60]. A review of relevant studies concluded that DM training over 6–14 sessions was more effective than systematic desensitization [50].…”
Section: Sop For Fod Treatment and Summary Of Empirical Datamentioning
confidence: 99%